Fintechs and the financial inclusion process in Peru - Salas Quenta, Anapierina Andrea (2022)
The objective of the study was to examine the relevance of fintech in the process of financial inclusion in Peru. The analysis was descriptive and was carried out through a documentary review. The scope of the investigation found that fintech companies aim to serve segments not covered by traditional banking and have great development potential, as a result of the advantages of digitization and the use of innovation, open banking trends, and a cooperative model. Likewise, these companies face obstacles that have prevented further progress in financial inclusion, such as the absence of financial products that meet the needs and the high operational costs compared to the low profit margins, which represent the traditional assistance given to those of excluded segments. In conclusion, it is noted that Fintechs contribute to the process of financial inclusion in Peru by providing access to products and services to segments of the traditionally excluded population. In addition, they promote competition in the financial system by introducing products suited to the client's needs, in a more efficient manner. However, despite the advances in the sector, it is essential to generate more evidence around the impacts that fintechs have on the financial inclusion process.